Some Features of Modeling Ultrasound Propagation in Non-Destructive Control of Metal Structures Based on the Magnetostrictive Effect - Babak, Vitalii; Bohachev, Ihor; Zaporozhets, Artur; Khaidurov, Vladyslav; Havrysh, Valerii; Kalinichenko, Antonina (Electronics (Basel), 2023)
A method and mathematical models of direct and inverse problems of ultrasonic testing and diagnostics of complex metal structures for defects were developed and tested. A prototype of a system for magnetostrictive control of elements of the objects under study was manufactured and experimentally tested. Mathematical simulation of ultrasonic testing processes using MATLAB and the COMSOL Multiphysics software environment was carried out. The adequacy of the mathematical models was verified by the results of their comparison with real physical experiments. Information support and a methodology that implements it was developed, which ensure the functioning of the control facilities for these objects based on the use of small-aperture magnetostrictive transducers. The mathematical identification of the vibration generator in complex building structures was developed, which consists in finding the locations of the generator of ultrasonic vibrations, as well as the characteristics of this vibration generator based on data obtained from sensors in the form of time series.